A new species of Uleiorchis (Gastrodieae, Orchidaceae) from the Brazilian Amazon - Cardoso, André Luiz De Rezende; Ilkiu-Borges, Anna Luiza; Rodrigues, Tarcísio Magevski (Phytotaxa, 2015)
A new species of Uleiorchis from Serra dos Carajás National Forest, Pará, Brazil, is described. This is the fourth species of this mycoheterotrophic genus. The species is illustrated, its affinities with related species are discussed, and a key to the species of the genus is presented. The new species differs from U. ulei, U. pratënsis and U. liesneri by the extremely elongated pedicel, the ligulate lip with a distal round dilatation, and by the elliptic, smooth stigmatic zone.